Thymoma mimicking an aortic aneurysm: always expect the unexpected. Issue 7 (17th July 2019) - Michaux, Dario; Berzenji, Lawek; Keulen, Lotte; Rodrigus, Inez
Abstract : Thymic epithelial tumours (TETs) are rare lesions that represent less than 1% of all malignancies in adults. Presentation occurs in three ways: asymptomatic, with local thoracic symptoms or with paraneoplastic symptoms. Heterotopic ossifications are rare histological features in neoplasms and non-neoplastic lesions. Here, we present a 49-year-old male patient with a thymoma type B2 mimicking an aortic aneurysm. Alongside the thymoma, a cholesterol granuloma with unusual ossification features was found as well. This clinical presentation and pathological diagnosis are unusual findings.